The Jungle Book - Rudyard Kipling; Rudyard Kipling (UK Oxford University Press, 2025)
The Jungle Book is a live-action/CGI fantasy film that retells the story of Mowgli, an orphaned human boy who, guided by his animal guardians, sets out on a journey of self-discovery while